2004
DOI: 10.1104/pp.103.030940
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Family of Transporters Mediating the Transport of Glutathione Derivatives in Plants

Abstract: Uptake and compartmentation of reduced glutathione (GSH), oxidized glutathione (GSSG), and glutathione conjugates are important for many functions including sulfur transport, resistance against biotic and abiotic stresses, and developmental processes. Complementation of a yeast (Saccharomyces cerevisiae) mutant (hgt1) deficient in glutathione transport was used to characterize a glutathione transporter cDNA (OsGT1) from rice (Oryza sativa). The 2.58-kb full-length cDNA (AF393848, gi 27497095), which was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 53 publications
2
78
0
Order By: Relevance
“…Thus, the glutathione uptake capacity was observed only when the yeasts were grown in a sulfur-deprived medium (SD-S) where the only source of sulfur is glutathione, confirming previous results (Bogs et al, 2003;Zhang et al, 2004). Concentration dependence studies showed that the initial rate of [ 3 H]GSH uptake (measured within the first 3 min of incubation) was not fully saturable up to 5 mM (Fig.…”
Section: Atopt6supporting
confidence: 73%
See 1 more Smart Citation
“…Thus, the glutathione uptake capacity was observed only when the yeasts were grown in a sulfur-deprived medium (SD-S) where the only source of sulfur is glutathione, confirming previous results (Bogs et al, 2003;Zhang et al, 2004). Concentration dependence studies showed that the initial rate of [ 3 H]GSH uptake (measured within the first 3 min of incubation) was not fully saturable up to 5 mM (Fig.…”
Section: Atopt6supporting
confidence: 73%
“…The Saccharomyces cerevisiae OPT1 protein was reported to transport the pentapeptides YGGFL and YGGFM (Leu-and Met-enkephalin;Hauser et al, 2000), reduced glutathione (GSH), oxidized glutathione (GSSG), and glutathione conjugates (Bourbouloux et al, 2000). Likewise, BjGT1, an OPT member from Indian mustard (Brassica juncea), and OsGT1, an OPT homolog from rice (Oryza sativa), were shown to transport GSSG and GS conjugates (Bogs et al, 2003;Zhang et al, 2004). In this respect, the OPT family resembles the last family of Arabidopsis peptide transporters, AtMRP1-4, which mediates the transport of GS conjugates (Lu et al, 1997(Lu et al, , 1998Sanchez-Fernandez et al, 1998).…”
mentioning
confidence: 99%
“…In this process sulfur is fixed as cysteine by the plants after a process of reduction (Saito, 2000). Cysteine is the initial material for the production of reduced glutathione, which is responsible for detoxify cells through the elimination of free radicals and reactive species that accumulate during different types of stress (Saito, 2004;Zang, 2004). According to Tohbe et al, (1998), exogenous applications of reduced glutathione induced bud breaking on buds of grapevines of Cv.…”
Section: Resultsmentioning
confidence: 99%
“…Later, OPT orthologs were identified in higher plants (Arabidopsis OPT1-OPT9, rice GT1, and Brassica juncea GT1) by sequence similarity searches using the complete sequence of the C. albicans OPT1 gene [73], or by RT-PCR, using primers corresponding to the conserved regions [74,75]. None of the OPT members show any significant sequence similarity to known PTRs.…”
Section: Opt Familymentioning
confidence: 99%